REPRESENTASI DUNIA NYATA DALAM DONGENG NEZUMI NO YOMEIRI - Novi Andari; Cuk Yuana (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
Abstract. This paper reports a mimetic approach to a Japanese fairy tale (mukashi banashi)  entitled ‘Nezumi no yomeiri.’ Mimetic approach to literary criticism assumes that a work of literature is an image of nature or description of the world and human life in the universe. Its proponents, Plato and Aristotle, proposed that literary works were copies of the authors’ ideas, while the ideas themselves were copies from realities of human life itself.  Fairy tales are one type of literary work, which has originally been orally transmitted through generation. The question of the study is to what extent the fairy tale represents real world and universe. The study found that the animal characters (mouses) in the tale are presented to have human characteristics, think and act like human, and hold human values and morals. The study may give more insights to the function of literary works in real life. Keywords: mimetic approach, Japanese fairy tales